2023
DOI: 10.21037/hbsn-21-578
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic anatomical versus non-anatomical liver resection for hepatocellular carcinoma in the posterosuperior segments: a propensity score matched analysis

Abstract: Background: Since laparoscopic anatomical resection (LAR) for tumors, especially located in the posterosuperior (PS) segments of the liver remains difficult, laparoscopic non-anatomical resection (LNAR) are generally preferred. To compare the clinical outcomes between LAR and LNAR for hepatocellular carcinoma (HCC) located in the PS segments.Methods: We retrospectively reviewed the data for 1,029 patients who underwent hepatectomy for HCC between 2004 and 2018. Of 167 patients who underwent laparoscopic hepate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Lee et al . 10 compared laparoscopic anatomical resection (LAR) with laparoscopic nonanatomical resection (LNAR) for posterior segment (PS) HCC using PSM and found that LNAR is a safe and feasible procedure with comparable oncological outcomes to LAR. Therefore, LNAR can be considered when the tumor is located in the PS and LAR cannot be performed.…”
mentioning
confidence: 99%
“…Lee et al . 10 compared laparoscopic anatomical resection (LAR) with laparoscopic nonanatomical resection (LNAR) for posterior segment (PS) HCC using PSM and found that LNAR is a safe and feasible procedure with comparable oncological outcomes to LAR. Therefore, LNAR can be considered when the tumor is located in the PS and LAR cannot be performed.…”
mentioning
confidence: 99%